Organização de uma cartilha para valorização da arte em miniatura sacra missioneira do museu Monsenhor Estanislau Wolski Santo Antônio das Missões - RS - Lopes, Michele Moraes (2016)
This research aims to discuss the display proccess of a cutural pratrimony art collection, located at Miniatura Sacra Jesuítica Guarani in the city's museum, Monsenhor Estanislau Wolski. The museum, located at Santo Antônio das Missões, Rio Grande do Sul, Brazil, has an unique collection of sculptures from the VII and XVIII centuries. The subject's importancy is related to the need that Santo Antônio's community has to give value, preserve and divulge its local cultural heritage. The local people need to express their feelings of belonging to a missionary past through the appreciation of the miniature sculptures in display in its museum. So the present work intends to organize text book to improve knowlodge about the miniature sculptures in display at Santo Antônio's museum, reeinforcing the historical origins of Santo Antônio's comunnity through heritage education, aiming to recognize, give value and dislose the missionary cultural patrimony. The miniatures show a production with more liberty and a domestic cult, where traces indians can shown a deep faith, the personification of the guarani culture, transforming the christian iconography, different from the images presented in other churches.